Enhancement of Cisplatin-Mediated Apoptosis in Ovarian Cancer Cells through Potentiating G2/M Arrest and p21 Upregulation by Combinatorial Epigallocatechin Gallate and Sulforaphane. (17th February 2013) - Chen, Huaping; Landen, Charles N.; Li, Yuanyuan; Alvarez, Ronald D.; Tollefsbol, Trygve O.
Abstract : Advanced-stage ovarian cancer is characterized by high mortality due to development of resistance to conventional chemotherapy. Novel compounds that can enhance the efficacy of conventional chemotherapy in ovarian cancer may overcome this drug resistance. Consumption of green tea (epigallocatechin gallate, EGCG) and cruciferous vegetables (sulforaphane, SFN) is inversely associated with occurrence of ovarian cancer and has anticancer effects through targeting multiple molecules in cancer cells. However, the effects of EGCG and SFN combinational treatment on ovarian cancer cells and on efficacy of cisplatin to these cells are unknown. In this study, EGCG or SFN was used to treat both cisplatin-sensitive (A2780) and cisplatin-resistant (A2780/CP20) ovarian cancer cells alone or in combination with cisplatin. We found that EGCG and SFN combinational treatment can reduce cell viability of both ovarian cancer cell lines time- and dose-dependently. Furthermore, EGCG and SFN combinational treatment can enhance cisplatin-induced apoptosis and G2/M phase arrest, thereby enhancing the efficacy of cisplatin on both cisplatin-sensitive and cisplatin-resistant ovarian cancer cells. EGCG and SFN combinational treatment upregulated p21 expression induced by cisplatin in cisplatin-sensitive ovarian cancer cells, while p27 expression was not regulated by these treatments. Collectively, these studies provide novel approaches to overcoming cisplatin chemotherapy resistance in ovarian cancer.